2022
DOI: 10.5009/gnl220005
|View full text |Cite
|
Sign up to set email alerts
|

Early Infliximab Trough Levels Predict the Long-term Efficacy of Infliximab in a Randomized Controlled Trial in Patients with Active Crohn’s Disease Comparing, between CT-P13 and Originator Infliximab

Abstract: Background/Aims: The clinical efficacy and safety of CT-P13 are comparable to originator infliximab for Crohn's disease in CT-P13 3.4 study (NCT02096861). We performed a multivariate logistic analysis to demonstrate the association between early infliximab trough levels and treatment outcomes of CT-P13 and originator infliximab. Methods:Early serum infliximab trough levels and anti-drug antibody (ADA) levels were compared between CT-P13 (n=100) and originator infliximab (n=98) groups. Receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…48,49 Table 1 provides an overview of infliximab target concentrations identified from prospective studies and post hoc analysis of RCTs during both induction and maintenance therapy. 10,13,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] Post hoc analysis of the pivotal ACCENT I and ACCENT II trials in CD showed that infliximab trough concentrations $3.5 and $7.2 mg/L at week 14 were predictive of clinical response at week 54 and combined fistula response and CRP normalization (composite remission) at week 14, respectively. 10,86 Also, infliximab trough concentrations $20.2 mg/L at week 2 and $15 mg/L at week 6 were associated with composite complete remission at week 14.…”
Section: Ibdmentioning
confidence: 99%
“…48,49 Table 1 provides an overview of infliximab target concentrations identified from prospective studies and post hoc analysis of RCTs during both induction and maintenance therapy. 10,13,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] Post hoc analysis of the pivotal ACCENT I and ACCENT II trials in CD showed that infliximab trough concentrations $3.5 and $7.2 mg/L at week 14 were predictive of clinical response at week 54 and combined fistula response and CRP normalization (composite remission) at week 14, respectively. 10,86 Also, infliximab trough concentrations $20.2 mg/L at week 2 and $15 mg/L at week 6 were associated with composite complete remission at week 14.…”
Section: Ibdmentioning
confidence: 99%